Motion Vector Estimation Using Hexagon Diamond Search Algorithm: Implementation and performance - Sarban Singh, Ranjit Singh (2009)
This thesis proposes modelling of fast unrestricted hexagon search (FUHS) and unrestricted hexagon-diamond search (UHDS16) algorithms for motion estimation, which is based on the theory and application of block-matching motion estimation. Both these algorithms are designed using 16 x 16 block size. In particular, the motion vector estimation, quality performance, computational complexity (search points), and elapsed processing time are emphasised.